Study of route of hysterectomy - Gupta, Dolly; Chandnani, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective is to study complication rate, advantages and outcome of different route of hysterectomy. Methods: A prospective study of 175 women over a period of 1 year i.e. from 01/01/2011 to 31/12/2011 SSG hospital, Vadodara. Depending on the patient profile, experience of surgeon optimum route of hysterectomy was decided. Results mean operating time in AH group was 68.4±14.4min, which was 80±10.3min, 115.8±40.6min and 148.8±25.5min in NDVH, LAVH and TLH group respectively. TLH was performed by consultants. Febrile morbidity was significantly high in AH (23%). Bladder and ureteral injuries were seen in 4% and 3% cases of NDVH and AH group. Wound complications were seen in AH (10%), whereas vault complications were higher in TLH. The hospital stay was shortest in TLH. Women with TLH had early ambulation, early resumption to normal diet, early return to routine work and better sexual function. Conclusions: Women with excessively enlarged uteri, significant pelvic pathology, or cancer are obvious candidates for AH. On the other hand, VH is frequently chosen for the small uterus in a multiparous woman with a large pelvis and no prior pelvic inflammatory disease or surgery. Although TLH, LAVH have significantly lower complication rate than AH, but overall cost is higher owing to the high operating room charges. The final selection of hysterectomy route should be based on surgeon’s experience and indication for surgery.